Abdominal aorta interruption and CHD. (30th December 2014) - Oliveira, Lia; Torres, Erica; Anjos, Rui
Abstract We report a rare case of CHD and abdominal aorta interruption. Renal hypertension was the first sign of the abdominal aortic malformation. The aetiology of abdominal aortic interruption remains unclear, it could be congenital or acquired.